The Impact of Classroom Management and Motıvatıon on Students’ Achıevement - Lutfi Darmansyah; Kristanti Yuntoro Putri; Irwan Sulistyanto (Universitas Nahdatul Ulama Surabaya, 2023)
Abstract: The purpose of this study is to investigate the impact of classroom management and motivation on students’ achievement. This study was located at SMK Queen Al-Falah in class XI Multimedia with a total of 70 respondents. This study uses a quantitative correlation method with data collection techniques in the form of questionnaires and documentation. Meanwhile, multiple regression analysis was used in this study at a significance level of 0.05. This study found (1) there is no significant impact of classroom management on students' achievement with a significance value of 0.813> 0.05 (2) there is a significant impact of motivation on students' achievement with a significance value of 0.01 < 0.05 (3) there is a significant impact of classroom management and motivation on students' achievement with a significance value of 0.000 < 0.05. The correlation value R was 0.458 with a moderate category. While the R square was 0.209 which could be interpreted that classroom management and motivation contribute 20.9% on students' achievement.